Presumed Stroke in a Cat—A Case Report - Sorin Marian Mârza; Radu Lăcătuș; Felix Daniel Lucaci; Lucia Bel; Ștefania Dandea; Iulia Melega; Robert Cristian Purdoiu (Veterinary Sciences)
This paper presents a detailed imaging-based approach to the diagnosis and evaluation of suspected ischemic stroke in a cat. The study describes a 12-year-old cat presented to our clinic with symptoms such as wheezing and inspiratory dyspnea, but without neurological or behavioral abnormalities. A computed tomography (CT) scan of the head revealed rhinitis, cerebral atrophy, and hypodense lesions in the right frontal and parietal brain regions, primarily supplied by the middle and rostral cerebral arteries. The lesion distribution, combined with cerebral atrophy and nonspecific clinical presentation, supported a provisional diagnosis of ischemic stroke. This case underscores the value of advanced imaging techniques in detecting incidental cerebrovascular events in feline patients, where initial respiratory symptoms, rather than overt neurological deficits, prompted investigation.